Faktor-Faktor Yang Berpengaruh Dalam Penentuan Penyaluran Kredit Perbankan Studi Pada Bank Umum Di Indonesia Periode Tahun 2006 - 2011 - Agus Murdiyanto (Conference In Business, Accounting, And Management (CBAM), 2012)
This study aims to analyze the effect of third-party funds (DPK), Adequasi Capital Ratio (CAR), Non Performing Loan (NPL), interest rate of Bank Indonesia Certificates (SBI) for Banking Credit Distribution. The data used are secondary data from Bank Indonesia include the National Banking Indicators, Indonesia Banking Statistics, Statistics Indonesia Monetary Economics, Banking Supervision Report. Test Results Statistikc independent sample t-test showed the influence of hypothesis testing can be inferred deposits to credit deposits partially variables significant positive impact on the credit variable. Testing hypotheses CAR effect on credit can be inferred by partial variable CAR significant negative effect on the credit variable. Testing hypotheses about the impact of NPLs to loans concluded NPL variable partially significant negative effect on the credit variable. Testing hypotheses about the impact of interest rates on loans concluded SBI partially SBI variables have a significant positive impact on the credit variable. Results adjusted R2 of 0.996, this means that 99% of the variation can be explained by variations in the credit of the four independent variables DPK, CAR, NPL, the SBI rate. While the remaining 1% is explained by reasons - other causes outside the model.Keywords: Loans, DPK, CAR, NPL,SBI.